Evaluation of health resources expenditure in two groups of psychotic patients treated with olanzapine and typical neuroleptics in a Italian Mental Health Department in Calabria Region - Caputo, Anna; Guidi, Luca; Biricolti, Giovanni; Torchia, Sergio (Farmeconomia. Health economics and therapeutic pathways, 2008)
Numerous Italian and international trials have studied the global costs of treatment with olanzapine and typical neuroleptics. Our analysis confirms those results. In our study, treatment with olanzapine, as compared to typical neuroleptics, was associated with a greater reduction in emergency interventions (hospitalisations), with an increased use of rehabilitation services and with a small increase in the number of working days. The differences between the two groups for this variable were not great, while the differences in the assessment scores appeared important and statistically significant. The results of present study are relative to the practice of one Italian Mental Health Department and, for this reason, cannot be generalized. Anyway, they are another indication of increased efficiency of atypicals treatment over older neuroleptics in schizophrenia.